EFEKTIVITAS PEMBELAJARAN RENANG BERBASIS PERMAINAN AIR DALAM MENINGKATKAN KOORDINASI MOTORIK ANAK USIA DINI - Dewi, Komang Ayu Krisna; Indrawan, I Ketut Addy Putra; Juliartha, I Made Semarawima (EDUKIDS : Jurnal Inovasi Pendidikan Anak Usia Dini, 2025)
The coordinative abilities of swimming extracurricular participants at SDN 1 Batuagung remain low, as indicated by uncoordinated movements, lack of enthusiasm, and the dominance of instructional methods that are not aligned with the characteristics of early childhood learners. This study aims to examine the effectiveness of a swimming learning approach based on water games in improving motor coordination in early childhood. A quantitative approach with a quasi-experimental one-group pretest-posttest design was used. The sample consisted of 15 children aged 6–8 years, selected purposively. The intervention was conducted over 4 weeks through 8 sessions of water games, such as swimming while catching balls, color obstacles, and relay swimming with movement variations. Data were collected using a standardized observation sheet with a 1–5 scale, validated by experts. The paired sample t-test results showed a significant improvement in all aspects of motor coordination, with an average score increase of +1.4 points (p < 0.05). In this study, we found that a swimming learning approach based on water games significantly improves motor coordination in early childhood in an enjoyable, adaptive, and developmentally appropriate manner. These findings offer an innovative contribution to the development of physical education learning models in primary schools. ABSTRAK Kemampuan koordinatif peserta ekstrakurikuler renang di SDN 1 Batuagung masih tergolong rendah, ditandai oleh gerakan yang tidak terkoordinasi, kurangnya antusiasme, serta dominasi metode instruksional yang kurang sesuai dengan karakteristik anak usia dini. Penelitian ini bertujuan untuk menguji efektivitas pendekatan pembelajaran renang berbasis permainan air dalam meningkatkan koordinasi motorik anak usia dini. Penelitian menggunakan pendekatan kuantitatif dengan desain eksperimen semu tipe one group pretest-posttest design. Sampel terdiri dari 15 peserta ekstrakurikuler renang usia 6–8 tahun yang dipilih secara purposif. Intervensi dilakukan selama 4 minggu melalui 8 sesi permainan air seperti renang sambil menangkap bola, rintangan warna, dan relay variasi gerak. Instrumen pengukuran menggunakan lembar observasi terstandar berskala 1–5 yang telah divalidasi ahli. Hasil uji paired sample t-test menunjukkan peningkatan signifikan pada semua aspek koordinasi motorik dengan rata-rata selisih skor +1,4 poin (p < 0,05). Dalam penelitian ini kami menemukan bahwa pendekatan pembelajaran renang berbasis permainan air secara signifikan meningkatkan koordinasi motorik anak usia dini secara menyenangkan, adaptif, dan sesuai dengan tahap perkembangan mereka. Temuan ini menjadi kontribusi inovatif bagi pengembangan model pembelajaran PJOK di sekolah dasar.